-12=4(x-7)-8x
One solution was found :
x = -4
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
-12-(4*(x-7)-8*x)=0
Step by step solution :
Step 1 :
Equation at the end of step 1 :
-12 - (4 • (x - 7) - 8x) = 0
Step 2 :
Step 3 :
Pulling out like terms :
3.1 Pull out like factors :
4x + 16 = 4 • (x + 4)
Equation at the end of step 3 :
4 • (x + 4) = 0
Step 4 :
Equations which are never true :
4.1 Solve : 4 = 0
Hope this helps you, Have a nice day.
Answer:
A) 32, 40, 48, 56, 64, 72, 80
B) y-axis goes 4, 8, 12
x-axis goes 4, 8, 12, 16, 20
Answer:
D
Step-by-step explanation:
Here, we want to get the value of x;
To get this, we simply use one of the circle angle and arc properties
Mathematically;
arc MN = 2 * arc MLN
3x + 22 = 134/2
That will be;
3x + 22 = 67
3x = 67-22
3x = 45
x = 45/3
x = 15
Answer:
-2, -1/2
Step-by-step explanation: